Effect of pay-for-performance incentives on quality of care in small practices with electronic health records: A randomized trial - Bardach, Naomi S. (2013)
IMPORTANCE: Most evaluations of pay-for-performance (P4P) have focused on large-group practices. Thus, the effect of P4P in small practices, where many Americans receive care, is largely unknown. Furthermore, whether electronic health records (EHRs) with chronic disease management capabilities support small-practice response to P4P has not been studied. OBJECTIVE: To assess the effect of a P4P incentive on quality in EHR-enabled small practices in the context of an established quality improvement initiative. DESIGN: Cluster-randomized trial SETTING, PARTICIPANTS: Small (<10 clinicians) primary care practices in New York City from April 2009-March 2010. A city program had provided all participating practices with the same EHR with decision support and patient registry functionalities and quality improvement specialists offering technical assistance. INTERVENTION: Incentivized practices were paid for each patient whose care met the performance criteria, but they received higher payments for patients with comorbidities or who had Medicaid or were uninsured (maximum payments: $200/patient; $100,000/clinic). Quality reports were given quarterly to intervention and control groups. MAIN OUTCOMES AND MEASURES: Differences in performance improvement, from beginning to end of the study, between control and intervention practices on aspirin or anti-thrombotic prescription, blood pressure control, cholesterol control, and smoking cessation. Mixed effects logistic regression was used to account for clustering of patients within clinics, with a treatment by time interaction term assessing the statistical significance of the effect of the intervention. RESULTS: Participating practices (n=42 for each group) had similar baseline characteristics, with a mean (median) of 4592 (2500) patients at the incentive group practices and 3042 (2000) at the control group practices. Intervention practices had greater absolute adjusted improvement in rates of appropriate anti-thrombotic prescription (12.0% improvement vs. 6.0% improvement among controls, difference: 6.0% (2.2–9.7%), p=0.001 for intervention effect), blood pressure control improvement (no comorbidities: 9.7% vs. 4.2%, difference: 5.5% (1.6–9.3%), p=0.01 for intervention effect; with diabetes: 9.0% vs. 1.2%, difference: 7.8% (3.2–12.4%), p=0.007 for intervention effect; with diabetes and/or ischemic vascular disease: 9.5% vs. 1.7%, difference: 7.8% (3.0–12.6%), p=0.01 for intervention effect) and improvement in rates of smoking cessation interventions (12.4% vs. 7.7%, difference: 4.7% (−0.3–9.6%), p=0.02 for intervention effect). Intervention practices performed better on all measures for Medicaid and uninsured patients except cholesterol control, but no differences were statistically significant. CONCLUSION AND RELEVANCE: Among small EHR-enabled practices, a P4P incentive program compared with usual care resulted in modest improvements in cardiovascular care processes and outcomes. Since most proposed P4P programs are intended to remain in place more than a year, further research is needed to determine whether this effect increases or decreases over time. CLINICALTRIALS.GOV REGISTRATION #: NCT00884013